Climate and water-related vulnerabilities in refugee hosting communities in northern Jordan: Irbid and Ramtha municipalities - Adam-Bradford, A.; Schindler, Alexandra; Anagreh, Abdullah; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
Jordan is one of the most water-scarce countries in the world and hosts the second-highest share of refugees per capita in the world. A fast-increasing population, rapid urbanization, and extreme weather-related hazards, such as drought and flash floods, compound the risks to already vulnerable refugee-hosting communities in Jordan. The Jordanian government as well as humanitarian and development organizations have committed to addressing these challenges by prioritizing the design and implementation of disaster risk management models which include early warning/early action and anticipatory action strategies for climate response and resilience. To design and implement disaster preparedness strategies that are sustainable and inclusive, research on the specific vulnerabilities of communities is needed. This research report provides data on climate- and water-related vulnerabilities in refugee-hosting communities in Northern Jordan to inform disaster risk management, anticipatory action, and emergency preparedness strategies that improve long-term adaptation and climate resilience.